2016
DOI: 10.1002/ptr.5628
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment with Yupingfeng Formula for Recurrent Respiratory Tract Infections in Children: A Meta-analysis of Randomized Controlled Trials

Abstract: This meta-analysis aimed to evaluate the immunomodulating function of Yupingfeng Formula (YPFF) in children with recurrent respiratory tract infections (RRTIs). The PubMed, EMBASE, Cochrane Library, CNKI and WanFang databases were searched for randomized controlled trials comparing with and without YPFF for RRTIs in children. Twelve trials with 1236 patients were identified. Adjuvant treatment with YPFF significantly increased serum levels of IgA (weighted mean difference [WMD] 0.33 mg/mL; 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…Although lots of researches had confirmed the efficacy of YPFS, more mechanisms by which YPFS inhibit inflammatory response should be fully elucidated ( Chen et al, 2014 ; Song et al, 2016 ). In this study, we used network pharmacological analysis to investigate the mechanisms of YPFS acting on asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Although lots of researches had confirmed the efficacy of YPFS, more mechanisms by which YPFS inhibit inflammatory response should be fully elucidated ( Chen et al, 2014 ; Song et al, 2016 ). In this study, we used network pharmacological analysis to investigate the mechanisms of YPFS acting on asthma.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons may due to the underlying pathogenesis of AD recurrence is still unclear. YPFS as a potent TCM against allergic disorder, applied in remission phase has been proven efficient through thousands of years of Chinese history [11,12]. Revealing the pharmacological mechanism of YPFS against AD recurrence, may help us to improve understanding the mechanisms of AD recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence recently points to the important role of AS-IV in regulating Toll-like receptors (TLRs)-mediated NF-κB pathway to exert its pharmacological effects [8][9][10]. Yu-Ping-Feng-San (YPFS), a well-known traditional Chinese medicine (TCM), is clinically applied for allergic disorders with reduced relapse rates and recurring severity [11,12]. Our previous study elucidated that YPFS attenuated recurrent allergic inflammation of AD by repairing epithelial barrier defects in remission phase [13].…”
mentioning
confidence: 99%
“…A meta-analysis on YuPingFeng treatment of recurrent respiratory tract infections in children also provided some insights. 28 A total of 1,236 subjects in 12 randomized control trials (RCTs) were screened, with a 4-week to 3-month treatment period and a 6–12-month observation period. Compared with traditional therapy alone, combined treatment with YuPingFeng significantly increased serum levels of IgA, IgG, IgM, and CD3 + cells, and three of the studies demonstrated that treatment with YuPingFeng reduced the frequency of recurrent respiratory tract infections in children.…”
Section: Discussionmentioning
confidence: 99%